(untitled) (Oxford, 1997)
The main objective of this book os to introduce Indonesian students to the fascinating marine environment of the Indonesian archipelago. this book provides an overview of a number of coastal and marine environments of the Indonesian Archipelago, with a focus on ecological precesses.
Keywords: Marine ecology; Indonesia